Secondary school students’ competencies and motivation to engage in mathematical modelling tasks in a virtual learning environment - Cohen-Nissan, Orit; Kohen, Zehavit (Frontiers in Education, 2023)
This study explores secondary school students’ competencies and motivation to engage in mathematical modelling (MM) tasks in a Virtual Learning Environment (VLE). The study is based theoretically on the didactical modelling cycle and the sub-competencies required for its application, the situated expectancy-value theory, and the VLEs’ design literature. Participants were 770 ninth graders who took part in a 5-day online summer camp, designed as a VLE, aiming at introducing them to mathematics within the tech industry. Research tools include Padlet MM tasks and observations for assessing students’ MM sub-competencies, as well as a pre-post motivation questionnaire for assessing students’ motivation to engage in MM tasks within the VLE. Observations and motivation questionnaires were also used to identify design features of the VLE that support students’ competencies and motivation. Findings show students’ demonstration of diverse levels of MM sub-competencies in forming a mathematical model, and mainly moderate-high levels in solving mathematical questions within the model and in interpreting the results. Students improved their self-concept of ability and task difficulty expectancies, as well as their attainment and interest values of MM tasks. Finally, the VLE’s structured activities and learning materials, along with instructional support and collaborative learning, supported students’ demonstration of MM sub-competencies and motivation to engage in MM. The study contributes to the literature regarding students’ demonstration of MM sub-competencies and their motivation to engage in MM in a VLE setting.